IMPACT OF TRANSFORMATION TRENDS AND STRATEGIC CHALLENGES IN THE FIELD OF FINTECH INNOVATIONS ON THE FINANCIAL SECTOR OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the impact of transformational trends and strategic challenges in the field of fintech innovations on the financial sector of Ukraine. It was determined that the current trends in the development of the financial sphere are characterized by revolutionary changes in financial technologies, which results in a change in the way the financial sector functions and creates the need to rethink development strategies for Ukrainian financial institutions. The main transformational trends in the field of fintech innovations, such as the use of blockchain technologies, artificial intelligence, the Internet of Things, and the specifics of cyber security, are analyzed. Their potential and opportunities for improving financial services and optimizing processes in the financial sector of Ukraine were studied. The strategic challenges that arise in connection with these trends are considered, in particular, competition from new fintech startups, regulatory aspects and the need for investments in technological development. It was determined that financial institutions of Ukraine can use fintech innovations to improve their competitiveness and provide quality financial services to clients. It has been proven that one of the key advantages of fintech innovations is the increase in the availability of financial services for a wide range of consumers, which is especially relevant for Ukraine, where there is often a shortage of access to banking services in rural areas and among the poor. It was determined that fintech innovations allow for the formation of digital solutions that simplify access to finance, reduce costs and risks for users. The importance of cooperation between financial institutions and fintech startups is discussed, as the interaction between these entities can lead to synergies, where traditional financial institutions use startup innovations to improve their services and expand their product range. It has been proven that regulators should develop a flexible regulatory framework that would promote innovation, as well as guarantee stability and protection of consumer interests. The need for Ukrainian financial institutions to be ready for the implementation of changes and innovations and to work actively to ensure successful adaptation to this new economic environment has been determined. The importance of adapting the financial sector of Ukraine to modern technological and regulatory changes in order to ensure sustainable development and preservation of customer trust is determined.
Keywords: fintech innovations, financial sector, blockchain technologies, artificial intelligence, financial services.